Upas e hospitais metropolitanos: a terceirização do serviço público de saúde no estado de Pernambuco - Roriz, Semiramis de Moura (2017)
Based on changes created by administrated reform and creation of public qualification of social organization as a partnership between public administration and private institution, several qualified institutions emerged and began to execute public services. The purpose of this research is to analyze Health social organizations from the State of Pernambuco, focused on those which execute public services at Unidades de Pronto Atendimento and Hospitais Metropolitanos verifying if a partnership between public admiration and private institutions exist or if there is an outsourcing service from public administration. To do so, a deep analyze of Federal legislation as well State Legislation which qualify non-profit private institutions as social organizations were made as well a bibliographic review to find out if the link between qualified health institutions and the state of Pernambuco is classified as partnership or outsourcing. As for a conclusion, after an analyze of all arguments, it was verified that, as it was proposed by the state of Pernambuco, the health social organizations were not executing a public service as a partnership with the state of Pernambuco, instead such organizations were executing a service as an outsourcing organization.